The development and evaluation of the Slovenian version of the Early Childhood Oral Health Impact Scale (ECOHIS-SVN) - Likar Ostrc, Lenka (Zdravstveno varstvo, 2023)
Introduction: There has been no valid and reliable instrument available to measure the impact of oral health on the quality of life of Slovenian preschool children. The main aim of this study was to develop and evaluate the validity and reliability of the first Slovenian instrument assessing Oral Health-Related Quality of Life (OHRQoL) preschool children: the ECOHIS-SVN. Methods: The ECOHIS-SVN was developed using forward-backward translations and with the participation of children aged under six and their parents. The children's teeth were examined, and parents were asked to complete questionnaires, including the ECOHIS-SVN. The internal consistency of ECOHIS-SVN was evaluated through the calculation of Cronbach’s alpha (?), test-retest reliability with an intra-class-correlation coefficient (ICC), convergent validity with Spearman’s rank correlation (r) and criterion validity with the Mann-Whitney test. The association between the ECOHIS-SVN score and parents’ age, educational level, self-reported oral health and OHIP-SVN14 was estimated using multiple linear regression. Results: In the study, 255 children participated, with a mean age of 4.8 years (±0.8). The ECOHIS-SVN questionnaire was completed by the parents of all 255 children and re-filled by 71 parents. The results of the total ECOHIS-SVN scale include ?=0.85, ICC=0.85, and r=0.6-0.75. A statistically significant association was found between the ECOHIS-SVN and parents’ age and between the ECOHIS-SVN and parents’ OHIP-SVN14 in the whole group and in the subgroup of children with no teeth affected by cavitated caries (dmft=0) (p=0.025, p=0.028), respectively. Conclusion: ECOHIS-SVN enables further studies to assess the OHRQoL of preschool children in the Slovenian-speaking population
Keywords: kvaliteta življenja, povezana z ustnim zdravjem; oral health; oral health-related quality of life (OHRQoL); predšolski otroci; preschool children; questionnaires; reliability; Slovenia; Slovenija; ustno zdravje; validity; veljavnost; vprašalniki; zanesljivost